2015
DOI: 10.1177/0310057x1504300206
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the APACHE II Score at ICU Discharge in Predicting Post-ICU Mortality and ICU Readmission in Critically Ill Surgical Patients

Abstract: In this study, we evaluated the efficacy of the discharge Acute Physiology and Chronic Health Evaluation (APACHE) II score in predicting post-intensive care unit (ICU) mortality and ICU readmission during the same hospitalisation in a surgical ICU. Of 1190 patients who were admitted to the ICU and stayed >48 hours between October 2007 and March 2010, 23 (1.9%) died and 86 (7.2%) were readmitted after initial ICU discharge, with 26 (3.0%) admitted within 48 hours. The area under the receiver operating character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(82 citation statements)
references
References 26 publications
3
66
0
1
Order By: Relevance
“…Several pediatric intensive care units (PICU) have adopted the Pediatric Risk of Mortality (PRISM), [9,10] Pediatric Index of Mortality (PIM), [11,12] or Acute Physiology and Chronic Health Evaluation II score (APACHE II) [13] to assess the severity of sepsis in pediatric patients. However, these indices involve multiple systematic parameters and complex computation; this might not be ideal for the clinical use in pediatric sepsis patients, as their care typically requires quick clinical judgment.…”
Section: Introductionmentioning
confidence: 99%
“…Several pediatric intensive care units (PICU) have adopted the Pediatric Risk of Mortality (PRISM), [9,10] Pediatric Index of Mortality (PIM), [11,12] or Acute Physiology and Chronic Health Evaluation II score (APACHE II) [13] to assess the severity of sepsis in pediatric patients. However, these indices involve multiple systematic parameters and complex computation; this might not be ideal for the clinical use in pediatric sepsis patients, as their care typically requires quick clinical judgment.…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Angus et al (19), the APACHE II score was also predictive of 1-year mortality (AUC of 0.671) in patients undergoing liver transplants. In contrast, a study by Lee et al reported no relation between the scores calculated on admission and post-discharge mortality (40). Lower diagnostic accuracy in predicting long-term mortality could be due to various reasons.…”
Section: Discussionmentioning
confidence: 87%
“…The treatment implemented during ICU stay, eventual complications and the quality of the follow-up care and rehabilitation, in uence the patient's outcome and can change the results provided by the scoring systems. Lee et al found that the discharge APACHE II score was a good predictor of post-ICU mortality and readmission (40). Therefore, it would be more reasonable to focus on the scores calculated to estimate the long-term prediction of the patients on their discharge from the ICU.…”
Section: Discussionmentioning
confidence: 99%
“…Readmission to ICU is associated with higher mortality risk than the initial admission (35). Considering the funding for ICU services which consumes substantial amount of health resources, a decrease in the readmission to ICU rates can be used as a hospital performance indicator (36)(37)(38). The first step of reducing the rates of readmission to ICU process is to anticipate the patients who would be readmitted to ICU priorly and improve general wards healthcare quality (39-41).…”
Section: Resultsmentioning
confidence: 99%